Monetary policy, crisis and capital centralization in corporate ownership and control networks: A B-Var analysis - Emiliano Brancaccio; Raffaele Giammetti; Milena Lopreite; Michelangelo Puliga (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
Based on a connection between network analysis and B-VAR models, this paper provides a first empirical evidence of the relationships between capital centralization expressed in terms of network control on one hand and monetary policy guidelines and business cycles on the other. Our findings suggest that a tightening monetary policy leads to a decrease in the fraction of top shareholders of network control which results in a higher centralization of capital; and that a higher centralization of capital, in turn, leads to a reduction of GDP with respect to its trend. These relations are confirmed both for the United States and the Euro Area.
Keywords: C11; D85; E32; E5; G34; 330; network analysis; ownership and control networks; centralization of capital; monetary policy; business cycle; financial crisis; B-VAR models